Clonazepam in the treatment of status epilepticus. (July 2015) - Shangguan, Yafei; Liao, Huan; Wang, Xuefeng
<x xml:space="preserve">Abstract</x> Status epilepticus (SE) is a common and serious neurological disorder. The prognosis of SE may be improved by effectively treating the disorder as early as possible. Clonazepam (CZP) has rarely been included in treatment guidelines for SE; however, this drug has been widely used in the treatment of SE patients and has unique advantages. Here, we elaborate on the clinical application of CZP in the treatment of SE and provide an effective and alternative treatment method for this disorder. We review selected literature, summarize action mechanisms, pharmacokinetics and clinical applications of CZP in the treatment of SE. We found that the effects of CZP are rapid and reliable and that adverse reactions are mild and transient. We conclude that CZP may be safely used to treat SE.